MAINSTREAMING DECOLONIAL PERSPECTIVES IN MEDIA AND COMMUNICATION - Poell, Thomas; Ong, Jonathan; Baykurt, Burcu; Guimarães Corrêa, Laura; Raman, Usha; Mutsvairo, Bruce; Mehta, Smith; Ye, Zhen; Nieborg, David; Caminhas, Lorena; et al. (AoIR Selected Papers of Internet Research, 2026)
Over the past two decades, there have been many calls and efforts to decolonize and de-westernize research in media and communication (Aouragh & Chakravartty 2016; Couldry & Mejias 2019; Ricaurte 2019). While these efforts have generated valuable academic centers, community-driven projects, and South-to-South networks (e.g., CARGC, FemLab, Tierra Comun), the field is still dominated by (implicit) universalist perspectives. Often the Anglo-American world is taken as the primary or only frame of reference in research on topics ranging from disinformation and platform governance to AI and new creator economies. Consequently, there is continuous friction between the main conceptual frameworks in the field and the experiences, interests, and concerns from the Global Majority world (Arora 2024; Lehuede 2024; Poell et al. 2024). Similar observations have been made regarding digital advocacy work, in which top-down, techno-legal solutions from the Global North tend to dominate, leaving little room for Global Majority innovations and priorities (Ong et al 2024). In the light of these concerns, this panel invites critical conversation about diverse initiatives of mainstreaming decolonial perspectives in media and communication. We are concerned that decolonization remains a specialization, rather than a force that transforms the field as a whole. Such a transformation is important for stakeholders around the globe. Universalism shuts out research and initiatives from most parts of the world in developing knowledge frames and proposing policy solutions. But, simultaneously, it prevents Global North researchers from understanding the specificity of media and communication in the US, Europe, and Australia. In other words, multiplying frames of reference and developing more bottom-up, locally-situated approaches also means critically reflecting on the particularity of Global North institutions and practices. In discussing how to mainstream, and–crucially–how not to apply decolonial perspectives in media and communication, we are confronted with a number of complex questions. First, while we advocate for more bottom-up, situated approaches, we also recognize the need to critically attend to the global dominance of major US-based tech companies (Couldry & Mejias 2019; Madianou 2024). How can we critically examine these unequal global power relations without reverting to a universalist and techno-solutionist mindsets that only reifies the centrality of US tech corporations and regulatory agencies? Second, from our perspective, it is vital that any efforts to mainstream decolonial approaches in our discipline should resist homogenization, bureaucratization, and tokenism in processes of movement-building. How do we develop more critical and granular analytics of what are better or worse methodologies of mainstreaming decolonial perspectives? What are the risks of using decoloniality as a “metaphor”? What are the differences between decolonial and anti-colonial approaches? Finally, the elephant in the room in any discussion of decoloniality is the inequality of resources and unjust practices of knowledge production in the discipline and higher education at large. To transform the field and multiply our frames of reference, we need global networks and institutions that “walk the talk” and promote just, equitable, and sustainable ways of working and collaborating. How do we share or redistribute resources in global collaborative projects? How can our discipline’s governance bodies and associations guard against tokenism and knowledge extractivism? What are examples of centers and networks in global tech studies that have successfully navigated situations of political conflict and instability, and what survival strategies can we learn from them? These are urgent questions today as global studies initiatives in the Global North are under attack from far-right conservative groups and governments, just as decolonization discourses have been hijacked by anti-democratic ethno-nationalists in the Global Majority (Chakravartty & Roy 2023). Drawing from five parallel research initiatives that aim to develop decolonial perspectives in media and communication, this panel will address these questions and involve the audience in a conversation about best practices: 1. “Local Specificity & Global Power Relations” addresses the conceptual, methodological, and political challenges that confront us when we try to multiply our frames of reference in media and communication research, while, simultaneously, attending to the global relations of power and dependency that define the contemporary digital media ecosystem. 2. “Decolonial Tech Policy: Engaging an Oxymoron?” reflects on South-to-South network-building as a method of “mainstreaming” decolonial perspectives in tech policy and digital advocacy spaces. 3. “Decaf Intersectionality, Soft Decolonialism and the Pact of Whiteness” addresses the whitewashing and the dilution of the ideas of intersectionality and of decolonisation, stressing the race and gender power dynamics in play when reflecting upon media, communications and culture, from global South perspectives. 4. “The Generative Power of Experience-in-Context” discusses insights from a grounded exploration of the lives of women engaged in informal labour, to feed back into [decolonial] theorizing about concepts like precarity, flexibility, networks, and identity. 5. “Decolonizing Fact-checking Through the Use of Nonprofessional Mediators” investigates the role of decolonized fact-checking interventions as potential tools to combat “fake news” in two politically unstable countries: Mali and Ethiopia.